(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article offers a review of Islamic sources and their interpretations of the main bioethical issues: from abortion, which is treated as a paradigmatic case, to euthanasia, organ transplantation and the donation of breast milk to milk banks. Not only the interpretations of the legal-theological tradition are presented, but also numerous stances of jurists and health organisations of the present time. A clear picture emerges of the underlying principles, trends and discussions on these issues in Islam today.